Estimating the costs of HIV clinic integrated versus non-integrated treatment of pre-cancerous cervical lesions and costs of cervical cancer treatment in Kenya. - Elisabeth L Vodicka; Michael H Chung; Marita R Zimmermann; Rose J Kosgei; Fan Lee; Nelly R Mugo; Timothy C Okech; Samah R Sakr; Andy Stergachis; Louis P Garrison; Joseph B Babigumira (PLoS ONE, 2019)
Objectives To estimate the modified societal costs of cervical cancer treatment in Kenya; and to compare the modified societal costs of treatment for pre-cancerous cervical lesions integrated into same-day HIV care compared to "non-integrated" treatment when the services are not coordinated on the same day. Materials and methods A micro-costing study was conducted at Coptic Hope Center for Infectious Diseases and Kenyatta National Hospital from July 1-October 31, 2014. Interviews were conducted with 54 patients and 23 staff. Direct medical, non-medical (e.g., overhead), and indirect (e.g., time) costs were calculated for colposcopy, cryotherapy, Loop Electrosurgical Excision Procedure (LEEP), and treatment of cancer. All costs are reported in 2017 US dollars. Results Patients had a mean age of 41 and daily earnings of $6; travel time to the facility averaged 2.8 hours. From the modified societal perspective, per-procedure costs of colposcopy were $41 (integrated) vs. $91 (non-integrated). Per-procedure costs of cryotherapy were $22 (integrated) vs. $46 (non-integrated), whereas costs of LEEP were $50 (integrated) and $99 (non-integrated). This represents cost savings of $25 for cryotherapy and $50 for colposcopy and LEEP when provided on the same day as an HIV-care visit. Treatment for cervical cancer cost $1,345-$6,514, depending on stage. Facility-based palliative care cost $59/day. Conclusions Integrating treatment of pre-cancerous lesions into HIV care is estimated to be cost-saving from a modified societal perspective. These costs can be applied to financial and economic evaluations in Kenya and similar urban settings in other low-income countries.